2018
DOI: 10.1103/physrevd.97.045003
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation-dissipation relation in accelerated frames

Abstract: An uniformly accelerated (Rindler) observer will detect particles in the Minkowski vacuum, known as Unruh effect. The spectrum is thermal and the temperature is given by that of the Killing horizon, which is proportional to the acceleration. Considering these particles are kept in a thermal bath with this temperature, we find that the correlation function of the random force due to radiation acting on the particles as measured by the accelerated frame, shows the fluctuation-dissipation relation. It is observed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…where ( * ) denotes the complex conjugate, then the structural physical approximation of partial transpose of ρ 12 is given by [24] In this section, we derive the criteria for the detection of bipartite negative partial transpose entangled states in arbitrary dimension employing the method of structural physical approximation (SPA) of partial transposition of any arbitrary dimensional quantum state.…”
Section: Preliminary Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…where ( * ) denotes the complex conjugate, then the structural physical approximation of partial transpose of ρ 12 is given by [24] In this section, we derive the criteria for the detection of bipartite negative partial transpose entangled states in arbitrary dimension employing the method of structural physical approximation (SPA) of partial transposition of any arbitrary dimensional quantum state.…”
Section: Preliminary Resultsmentioning
confidence: 99%
“…So the analysis of minimum eigenvalue of ρ out is needed. It has been found that SPA-PT method not only detect entanglement but also can be applied to estimate the optimal singlet fraction, entanglement negativity and concurrence of the two-qubit density matrix in an experiment [24,25]. H. T. Lim et.al.…”
Section: Introductionmentioning
confidence: 99%
“…Substitution of this in (C1) yields (10). Although the form of Green's function (10) is enough for our purpose, but for completeness we shall see that the same can be expressed in an another useful form.…”
Section: Appendix B: Finite Temperature To Zero Temperature Propagatomentioning
confidence: 99%
“…Apart from understanding this from the accelerated detector's perspective [7][8][9], recently it has been observed that the force due to radiation as measured by the accelerated frame satisfies quantum fluctuation-dissipation theorem [10]. This observation is quite analogous to the Brownian motion of a particle in a real thermal bath.…”
Section: Introductionmentioning
confidence: 97%
“…All these resemblance between these two facts is well compatible with the equivalence principle. Several recent investigations has been done related to the nature of the observed particles in this thermal bath [4][5][6][7]. A very recent investigation reveled that these particles can exhibit Brownian like motion in this thermal bath and satisfy the well known equilibrium fluctuation-dissipation theorem [4,6].…”
Section: Introductionmentioning
confidence: 99%